问题 解答题
化简求值.
(1)(-m4÷m22+(-2m)3•m2+(-m24÷m4,其中m=-1.
(2)(
2xy2
x+y
)3÷(
xy3
x2-y2
)2•[
1
2(x-y)
]2
,其中x=-
1
2
y=
2
3

(3)先化简,然后请你选择一个合适的x的值代入求值:
x2-4x
x+3
÷
4-x
x
答案

(1)(-m4÷m22+(-2m)3•m2+(-m24÷m4=m4-8m5+m4=2m4-8m5

把m=-1代入上式得:

原式=2×(-1)4-8×(-1)5=2+8=10.

(2)(

2xy2
x+y
)3÷(
xy3
x2-y2
)2•[
1
2(x-y)
]2=(
2xy2
x+y
)
3
×
(x2-y2)2
x2y6
1
4(x-y)2
=
2x
x+y

x=-

1
2
y=
2
3
时,

原式=

2×(-
1
2
)
-
1
2
+
2
3
=-6.

(3)

x2-4x
x+3
÷
4-x
x
=
x(x-4)
x+3
×
x
4-x
=-
x2
x+3

当x=1时,原式=-

12
1+3
=-
1
4

单项选择题
单项选择题